Family language policy : maintaining an endangered language in the home - Smith-Christmas, Cassie (Palgrave Pivot, 2016)
"Why some children being raised in multilingual environments use more of their minority language than others is an important question both for researchers and caregivers of multilingual children. This book sheds light on this question by exploring it through the lens of three siblings on the Isle of Skye, Scotland, who are being raised in an extended family where the adults are trying to maintain the endangered Scottish Gaelic language with them. However, despite the adults' best efforts, and despite the fact that the children attend a Gaelic immersion school, none of the children currently use very much Gaelic. Smith-Christmas looks at the adults' language practices with the children, as well as their language practices with each other and the language norms in the wider community, in order to explain why language maintenance is such a continual uphill struggle for this family"--